2000
DOI: 10.1002/1096-9128(200009)12:11<1019::aid-cpe518>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

MPJ: MPI-like message passing for Java

Abstract: SUMMARYRecently, there has been a lot of interest in using Java for parallel programming. Efforts have been hindered by lack of standard Java parallel programming APIs. To alleviate this problem, various groups started projects to develop Java message passing systems modelled on the successful Message Passing Interface (MPI). Official MPI bindings are currently defined only for C, Fortran, and C++, so early MPI-like environments for Java have been divergent. This paper relates an effort undertaken by a working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 7 publications
0
62
0
1
Order By: Relevance
“…Saikat et al [10] also showed that TCP forwarding scheme was successful at a average rate of 88% for existing NATs and a 100% for pairs of certain common type of NATs. These results show that running parallel processes over private clusters does not require a special mechanism or device and our scheme can be applied to many parallel systems such as OpenMP [11] and MPJ [12].…”
Section: Discussionmentioning
confidence: 96%
“…Saikat et al [10] also showed that TCP forwarding scheme was successful at a average rate of 88% for existing NATs and a 100% for pairs of certain common type of NATs. These results show that running parallel processes over private clusters does not require a special mechanism or device and our scheme can be applied to many parallel systems such as OpenMP [11] and MPJ [12].…”
Section: Discussionmentioning
confidence: 96%
“…In the experiment presented in this paper we have considered just Amazon's micro types (EC2 ID: t1.micro -613 MB RAM, 30 GB of EBS storage only, 1 core). Each instantiated VM uses Linux Cent OS 5 (64-bit), and it was configured with the necessary software, libraries like MPJ [27], and the bioinformatics applications. All instances are based on the same image (AMI ID ami-7d865614) and it was used to execute SciCumulus.…”
Section: Environment and Experiments Setupmentioning
confidence: 99%
“…subset of the MPJ speci cation [11]). The core behind the API implements appropriate message handling, and relies on three other modules.…”
Section: The P2p-mpi Middlewarementioning
confidence: 99%
“…The communication are hence almost as e cient as with the underlying MPI library, but the presence of an MPI library and system-dependent generated bindings reduce the portability advantage of Java programs. Later, MPJ [11] has been adopted by the Java Grande forum as a common MPI language bindings to Java, merging the above proposals. However, we know of very few MPJ implementations: mpiJava claims to move towards this speci cation, and recently, an implementation in pure Java from Vrije University [6] called MPJ/Ibis has been proposed.…”
Section: Mpi and Javamentioning
confidence: 99%